2006
DOI: 10.1002/anie.200502698
|View full text |Cite
|
Sign up to set email alerts
|

Apoptolidin: Induction of Apoptosis by a Natural Product

Abstract: Apoptolidin is a natural product that selectively induces apoptosis in several cancer cell lines. Apoptosis, programmed cell death, is a biological key pathway for regulating homeostasis and morphogenesis. Apoptotic misregulations are connected with several diseases, in particular cancer. The extrinsic way to apoptosis leads through death ligands and death receptors to the activiation of the caspase cascade, which results in proteolytic degradation of the cell architecture. The intrinsic pathway transmits sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(52 citation statements)
references
References 201 publications
0
51
0
1
Order By: Relevance
“…Syntheses of apoptolidinone A, the aglycone of 1, were reported by the groups of Sulikowsky [143], Crimmins [144], Nicolaou [138][139][140], and Koert [141,142]. In addition, several studies on the synthesis of fragments of apoptolidinones have been reported [137,[145][146][147][148][149][150][151][152][153][154][155].…”
Section: Methodsmentioning
confidence: 94%
“…Syntheses of apoptolidinone A, the aglycone of 1, were reported by the groups of Sulikowsky [143], Crimmins [144], Nicolaou [138][139][140], and Koert [141,142]. In addition, several studies on the synthesis of fragments of apoptolidinones have been reported [137,[145][146][147][148][149][150][151][152][153][154][155].…”
Section: Methodsmentioning
confidence: 94%
“…Aer ring closure of 11 using the Mo-catalyzed olen metathesis, 73 the resultant cyclolactam 12 was subjected to a stereocontrolled hydrogenation. Subsequent cleavage of the acetyl and triuoroacetyl groups with hydrazine at room temperature afforded Sch 38516 (8) in 63% yield (for three steps).…”
Section: Syntheses With Glycosyl Fluoridesmentioning
confidence: 99%
“…Discovery of natural products that can induce apoptosis of cancer cells has been a major research area in development of novel anticancer agents [43]. In 1998, Umezawa et al isolated hexadepsipeptides polyoxytoxins A and B from Streptomyces culture broth.…”
Section: Noncoded Caasmentioning
confidence: 99%
“…Evans and Weber used a diastereoselective aldol method of synthesizing MeBmt that provided the amino acid in high optical purity (>99% d.e.) after chromatography and recrystallization (Scheme 5.40) [43,142]. While the Evans synthesis provided MeBmt 162, efforts continue in search of a more efficient synthesis that will allow for the production of multigram quantities of MeBmt.…”
Section: Noncoded Amino Acids With Elaborate Side-chainsmentioning
confidence: 99%